Empirical study of relation measures of stable distributed stock returns - Belovas, Igoris; Kabašinskas, Audrius; Sakalauskas, Leonidas (Lietuvos matematikos rinkinys, 2008)
Relationships between financial instruments are very important in practical portfolio management. Under the assumption of stability, when the second moment does not exist, traditional relationship measures cannot be applied. In this paper we introduce new general correlation measures. Results of the empirical analysis of the selected equities from Baltic States market are given as an example.